2018
DOI: 10.1016/j.fsigen.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Allele and haplotype diversity of 12 X-STRs in Sardinia

Abstract: The analysis of clusters of tightly linked X-chromosome short tandem repeat (STR) markers can assist the interpretation of complex kinship cases. However, when linkage disequilibrium (LD) is present in the population of origin of tested individuals, haplotype rather than allele frequencies should be used in likelihood calculations. The diversity of twelve X-STRs arranged in four linkage groups (I: DXS10148-DXS10135-DXS8378; II: DXS7132-DXS10079-DXS10074; III: DXS10103-HPRTB-DXS10101; IV: DXS10146-DXS10134-DXS7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We study R st metrics produced in the software Arlequin [38] which give a measure of the genetic proximity of population and further use this information to combine populations into such larger super-populations. We illustrate that combing haplotype data from genetically similar population provides a lower degree of spurious linkage disequilibrium while still being able to accurately detect true patterns of association of alleles (see 887 Italy [42], Portugal [22], Sardinia [21], Serbia [23]…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We study R st metrics produced in the software Arlequin [38] which give a measure of the genetic proximity of population and further use this information to combine populations into such larger super-populations. We illustrate that combing haplotype data from genetically similar population provides a lower degree of spurious linkage disequilibrium while still being able to accurately detect true patterns of association of alleles (see 887 Italy [42], Portugal [22], Sardinia [21], Serbia [23]…”
Section: Discussionmentioning
confidence: 98%
“…We refer to these data as our primary data set. Additional publications [14][15][16][17][18][19][20][21][22][23][24][25] listed in Supplementary Table 1, with only cluster specific haplotypes were considered for a subset of the analyzes. We refer to these data as our secondary data set.…”
Section: Datamentioning
confidence: 99%
“…The Investigator Argus X-12 kit was also used in this study, and 914 complete haplotypes were obtained for the markers included in the kit. Knowing the uniqueness provided by the X-STR markers, several research groups conducted studies to assess the population distribution of countries such as Brazil, Switzerland, Italy, India, Croatia, and countries on the African continent, among others [ 9 , 15 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Table 1 lists some population studies that explore X-STR markers, published in the last ten years.…”
Section: Population Geneticsmentioning
confidence: 99%
“…DXS10146 and DXS10135 markers presented 38 alleles, revealing the most polymorphic alleles. The most informative locus among the population studies mentioned is DXS10135, shown in 11 different studies [ 9 , 15 , 35 , 39 , 40 , 42 , 43 , 45 , 46 , 49 ]. This is due to the high PIC (polymorphism information content) value of this locus in the different populations [ 51 ].…”
Section: Population Geneticsmentioning
confidence: 99%
“…These uniparental markers can be used in those cases of human identification where one of the alleged parents is not available for the DNA testing. The missing alleged parent can be replaced by a female or a male relative who has common ancestors on maternal or paternal lineage, if uni-parental markers are used [3][4][5][6]. When we talk about parentage DNA testing, in difficult cases the expert is dealing with one, two or three inconsistencies between the child and the alleged father [7][8][9].…”
Section: Introductionmentioning
confidence: 99%